2021
DOI: 10.6007/ijarped/v10-i1/8846
|View full text |Cite
|
Sign up to set email alerts
|

Primary School Teachers' Usage and Perception of Online Formative Assessment Tools in Language Assessment

Abstract: Language Assessment is still very important and needs to be continued in helping the teachers to understand their learner's performance and maintained it even though the schools are closed temporarily. This study is to explore the use of Online Formative Assessment Tools (OFAT) to ESL young learners' language performance. A descriptive mixed method design was implemented in this study to analysed the data. A set of questionnaires and three open-ended questions was distributed to 100 English teachers to two dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…Such poor networks could result into loss of internet service and connectivity and eventual wiping out of answers students have already provided. This is in line with the findings of Mariam (2021) and Fedelis and Harwati (2021) that poor internet connectivity is perceived as a challenge to usage of online assessment of learning by teachers. Again, the finding showed that teachers perceive online assessment to be only suitable for closed questions with a limited range of possible answers.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Such poor networks could result into loss of internet service and connectivity and eventual wiping out of answers students have already provided. This is in line with the findings of Mariam (2021) and Fedelis and Harwati (2021) that poor internet connectivity is perceived as a challenge to usage of online assessment of learning by teachers. Again, the finding showed that teachers perceive online assessment to be only suitable for closed questions with a limited range of possible answers.…”
Section: Discussionsupporting
confidence: 92%
“…They were equally of the opinion that adequate guidance was not provided; therefore, they preferred to avoid using online exams and quizzes.The findings of Mariam (2021) revealed that the teachers' perception of online assessment includes but are not limited to: lack of physical interaction, poor assessment of speaking and translation courses, high risk of cheating and plagiarism, technical difficulties, and problem of guarantying the integrity of online assessment. The findings of Fedelis and Harwati (2021) equally revealed that teachers perceive online assessment as difficult due to slow network transmission, lack of facilities, accessibility to reliable gadgets and time needed by teachers to apply online assessment tools. The challenge of network is further collaborated by Emmanuel (2020), who stated the teachers found it difficult to upload large notes.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, numerous instructors consider formative assessments as a tool to measure students’ learning, while missing out on its teaching potential. Testing and teaching can be one or the same which will be discussed further in this research (Remmi & Hashim, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The current study fills an important research gap: very few studies have been conducted on teachers' perceptions of online and offline assessment practices. It is essential to identify teachers' views on online formative assessments in order to find ways to make necessary and additional improvements (Remmi & Hashim, 2021). In the context of ESL and EFL tertiary-level classrooms, many studies have been conducted to understand teachers' assessment practices (Cheng et al, 2004;Cheng & Wang, 2007;Cumming, 2001).…”
Section: Literature Reviewmentioning
confidence: 99%